Pengaruh Rekrutmen, dan Seleksi terhadap Kinerja karyawan pada UMKM Toko E3 Surabaya - Hafid, Mohammad; Hafid, Mohammad; Hafid, Mohammad (Research Journal of Social Science and Economics, 2025)
From the achievement of the target in September-December 2022, there was a decrease so that it was suspected that there was a suboptimal employee performance. And to meet the needs of its employees, the store takes various ways, and from the results of the data obtained by researchers, it can be seen that there are still many employees who enter through the entrustment / relative route, while recruitment before selection also does not seem to be going well, where the percentage of good recruitment results that come alone, and advertising results are very small. This study aims to determine and analyze the effect of Recruitment and Selection on employee performance at MSMEs E3 Surabaya Store, and to find out the variables that have a dominant influence on employee performance. The research method used in this study is quantitative research using questionnaires as data collection instruments. The population used in this study was all employees at the E3 Store MSMEs and used saturated sampling techniques or census with a total of 44 employees. The results of this study show that Recruitment has a positive and significant influence on employee performance then Ho is rejected and Ha is accepted, Selection does not have a positive and significant influence on employee performance so that Ha is rejected, and Recruitment, Selection has a joint or simultaneous effect on employee performance then Ho is rejected and Ha is accepted, then the variable that has a dominant influence is Recruitment